2014
DOI: 10.1111/1756-185x.12482
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mediterranean fever gene mutations in Egyptian children with inflammatory bowel disease

Abstract: IBD patients, in populations with a high background carrier rate of MEFV variants, should be screened for MEFV gene mutations, especially those diagnosed as indeterminate colitis. Testing larger numbers of healthy Egyptian children for MEFV gene mutation is important to further determine the allele frequency in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In the present study, 11 patients (22.9%) were also diagnosed with FMF confirmed by genetic testing. This observation agrees with the study by Salah et al[ 26 ] conducted at our institute, which reported a significant association between MEFV gene mutation and IBD in Egyptian children, especially in patients with indeterminate colitis (IBD-U)[ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 11 patients (22.9%) were also diagnosed with FMF confirmed by genetic testing. This observation agrees with the study by Salah et al[ 26 ] conducted at our institute, which reported a significant association between MEFV gene mutation and IBD in Egyptian children, especially in patients with indeterminate colitis (IBD-U)[ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in studies conducted in patients with IBD, the incidence of FMF was found between 5% and 25% [ 14 16 ]. Salah et al [ 17 ] analyzed the frequency of MEFV mutations in children with IBD and they found that 88% of the IBD patients carried the one of the MEFV mutations and especially common in indeterminate colitis. FMF should be considered in differential diagnosis especially in cases of early-onset and treatment-resistant IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on the frequency of MEFV gene mutations in IBD, rather than the cooccurrence or frequency of FMF in IBD. Only two studies discovered that MEFV gene mutation was highly frequent in IBD and reported other confusing factors such as kinship marriages or low mutation rates in control groups [ 16 , 17 ]. However, similar studies demonstrated that the frequency of MEFV gene mutations in IBD patients is not significant compared to the healthy population [ 10 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%